2019
DOI: 10.1002/eat.23201
|View full text |Cite
|
Sign up to set email alerts
|

Testing the specificity of interpretation biases in women with eating disorder symptoms: An online experimental assessment

Abstract: Objective Cognitive biases, such as memory, attention, and interpretation bias, are thought to play a central role in the development and maintenance of eating disorders (EDs). The aim of the present study was to investigate whether the interpretation bias is ED‐specific or can be generalized to comorbid disorder‐related threats in women with high levels of ED symptoms. Method In an online study, we measured interpretation bias using the modified Sentence Word Association Paradigm (SWAP), comparing women with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Research has found that IBs not only often correlate with symptoms of psychopathology (e.g., Korn, Dietel, & Hartmann, 2020;, but also predict future symptoms and even the onset of a disorder (Kleim et al, 2013;Woud et al, 2014). Further, experimental manipulation of IBs can lead to changes in analog, and over time, actual symptoms of psychopathology (e.g., Joormann et al, 2015;Van Bockstaele et al, 2020) albeit not consistently across the literature (Fodor et al, 2020;Jones & Sharpe, 2017).…”
Section: Scrambled But Valid? the Scrambled Sentences Task As A Measu...mentioning
confidence: 99%
“…Research has found that IBs not only often correlate with symptoms of psychopathology (e.g., Korn, Dietel, & Hartmann, 2020;, but also predict future symptoms and even the onset of a disorder (Kleim et al, 2013;Woud et al, 2014). Further, experimental manipulation of IBs can lead to changes in analog, and over time, actual symptoms of psychopathology (e.g., Joormann et al, 2015;Van Bockstaele et al, 2020) albeit not consistently across the literature (Fodor et al, 2020;Jones & Sharpe, 2017).…”
Section: Scrambled But Valid? the Scrambled Sentences Task As A Measu...mentioning
confidence: 99%
“…Research has found that IBs not only often correlate with symptoms of psychopathology (e.g., Korn, Dietel, & Hartmann, 2020;, but also predict future symptoms and even the onset of a disorder (Kleim et al, 2013;Woud, Zhang, Becker, McNally, & Margraf, 2014). Further, experimental manipulation of IBs can lead to changes in analog, and over time, actual symptoms of psychopathology (e.g., Hirsch et al, 2018;Joormann, Waugh, & Gotlib, 2015;Mathews & Mackintosh, 2000;Van Bockstaele, Clarke, Notebaert, MacLeod, & Salemink, 2020).…”
Section: Scrambled But Valid? the Scrambled Sentences Task As A Measure Of Interpretation Biases In Psychopathology: A Systematic Reviewmentioning
confidence: 99%
“…While not a limitation per se, a further consideration is that Emotional BADE Task scenarios focus on themes of interpersonal rejection/social failure. A stronger relation between disordered eating and interpretation processes might have been found using scenarios with more eating‐disorder‐specific content (Korn, Dietel, & Hartmann, 2020). Other potential limitations stem from our use of an MTurk sample, which may not be representative of nonclinical populations experiencing eating disorder symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…using scenarios with more eating-disorder-specific content (Korn, Dietel, & Hartmann, 2020). Other potential limitations stem from our use of an MTurk sample, which may not be representative of nonclinical populations experiencing eating disorder symptoms.…”
Section: Discussionmentioning
confidence: 99%